Numerical simulation of a low aspect ratio wing at low Reynolds number - Suliman , M. M. Ali; Omar, Ashraf Ali; Syed Mohamed Ali, Jaffar; M. Syuhairi |, M. Husain (2013)
In this work the numerical simulation of aerodynamic performance of low aspect ratio wings at low Reynolds numbers applicable to micro aerial vehicle is carried out. Commercial software STAR-CCM+ was used to simulate the flow and predict the aerodynamics performances of the low aspect ratio wing. Results were presented in terms of pressure coefficient distribution, flow visualization, lift and drag coefficients for angle of attacks ranging from 0˚ to 18˚ and Reynolds numbers ranging from 104 to 105 Keywords: Rectangular planform wing; Tip vortices; Flow separation . The results showed that, for rectangular planform wing, the distribution of the pressure is dominated by vortices. The results also showed the formation of tip vortices at lower Reynolds number for rectangular wing configuration. It is evident from the results that the type of wing configurations plays a very important role in delaying or preventing the flow separation.